2018
DOI: 10.2298/tsci160930012v
|View full text |Cite
|
Sign up to set email alerts
|

Fire extinction of forest fuels by droplets and water film

Abstract: The paper presents the experimental results about fire extinction in the model fire sites of forest combustible materials. We use the high-speed video recording tools during the experiments, as well as the system of multiphase media diagnostics based on panoramic optical flow visualization techniques. The presented experiments prove that it is possible to extinguish the forest combustible material (FCM) by small amount of water. The study considers several ways to stop FCM thermal decomposition: by individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 12 publications
(32 reference statements)
0
18
0
5
Order By: Relevance
“…In the early works (in particular, [7][8][9][10][11][12]) the authors have shown results of experimental and theoretical research of suppression of burning of typical forest fuel materials (FFM) of drops, films, aerosols, unsprayed water arrays (including with the use of specialized fire extinguishing additives). The main focus of the research during 2014-2016 was on the creation of technology for extinguishing forest fires by droplet flows, distributed in time and space.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the early works (in particular, [7][8][9][10][11][12]) the authors have shown results of experimental and theoretical research of suppression of burning of typical forest fuel materials (FFM) of drops, films, aerosols, unsprayed water arrays (including with the use of specialized fire extinguishing additives). The main focus of the research during 2014-2016 was on the creation of technology for extinguishing forest fires by droplet flows, distributed in time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Such flows can be created with specialized polydisperse spraying of water into the combustion zone from different heights relative to the surface of the forest. It has been found [7][8][9][10][11][12] that effective conditions for localizing the forest material combustion become possible with temperature decrease in the gas phase above the material surface as well as with blocking the oxidizer access to the combustion zone and the outflow of thermal decomposition products from the sample material into the gas phase. These conditions may be fulfilled by controlling the completeness of evaporation of the extinguishing liquid in the gas phase and on the surface of the pyrolyzing material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of the droplet diameter of easily volatile liquids leads to significant intensification of evaporation due to steam convection [30]. Gas-droplet flows are widely used for fire extinction and in solving environmental problems [31][32][33]. The measurement technique of the thermal imager is presented in [34].…”
Section: Introductionmentioning
confidence: 99%